Processing Plastik Waste into Creative Handicrafts to Reduce Plastik Waste in West Palimanan Village - Abu Lubaba; Farah Fadhilah; Wandi Hidayat (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2024)
Plastics waste is a major problem in environmental pollution, both land and sea pollution. Plastik waste has properties that cannot be decomposed and will decompose completely over a period of 80 to 300 years. This plastic waste has quite promising business potential so that we can process it into creative handicrafts. This creation of plastik waste has a selling value that generates profits. By using plastic waste, we can overcome the problem of environmental pollution and environmental sustainability. Apart from that, it increases the creativity of the local community and has very minimal capital. This research is about handling plastic waste which can provide added value to make handicrafts. The object of the research was carried out in West Palimanan Village with an observational approach to problems and intervention to the problems raised. In detail, the processing of plastik waste is powdered drink packaging. The intervention method was carried out by providing guidance to Mrs. Karsini in the Rahayu Block, West Palimanan Village, who works as a plastik waste craftsman. The approach was carried out over a period of 4 weeks on 30 November – 31 December 2020. The result of this activity was the formation of creative products in the form of bags, wallets, mats which had selling value and could be consumed by the public.